Influence of Financial Architecture, Corporate Social Responsibility on Company Value of Banking in Indonesia - Widnyana, I Wayan; I Wayan Sukadana; I Gede Putu Eka Budiyasa (Business and Entrepreneurial Review, 2023)
This study aims to analyze and explain the influence of the dimensions of financial architecture consisting of ownership structure, capital structure, and corporate governance as well as adding other variables namely CSR to company value of banking in Indonesia. This research was conducted on banks listed on the Indonesia Stock Exchange (IDX) for the period of 2018 - 2020 using secondary data sources, consisting of 81 banks, of which 76 banks as samples because they have complete data. The analytical method used is multiple linear regression analysis, multiple correlation analysis, determination analysis, and t-test. The results showed that the ownership structure, capital structure, corporate governance, and CSR had a positive and significant effect on company value of banking in Indonesia.